A novel effect of EGF on mRNA stability. - Jinno, Y (1988)
Expression of the epidermal growth factor (EGF) receptor gene is stimulated by EGF and the phorbol ester, 4 beta-phorbol 12-myristate 13-acetate (PMA). PMA elevates EGF receptor mRNA levels in human KB epidermoid carcinoma cells, but does not significantly affect the half-life of this mRNA when its decay is examined after the addition of actinomycin D. In contrast, EGF greatly prolongs the half-life of EGF receptor mRNA suggesting a possible mechanism for the stimulatory effect of EGF on EGF receptor mRNA levels. EGF also stabilizes beta-tubulin and beta-actin mRNAs but has very little effect on the degradation of total mRNA.